ANALISIS WACANA KRITIS PEMBERITAAN 100 HARI GEBRAKAN PRABOWO- GIBRAN DI DUNIA PENDIDIKAN PADA MEDIA KOMPAS.COM - Wiji Mustainah; Mukhlis; Eva Ardiana Indrariani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines media ideology in the coverage of Prabowo–Gibran’s 100 Days of Breakthroughs in Education on Kompas.com using Teun A. van Dijk’s Critical Discourse Analysis (CDA) model. Data consist of five news articles published between January and February 2025, selected through purposive sampling. The analysis was conducted qualitatively across three dimensions: text (macro, micro, and superstructure), social cognition, and social context. The findings reveal that the media do not merely report education policies but actively construct public opinion through linguistic strategies, issue framing, and rhetorical devices. While policies such as the 13-year compulsory education and teacher allowance improvements are portrayed as achievements, issues of educational equity and the welfare of honorary teachers are critically addressed. These results support earlier studies (Sari, 2020; Widodo, 2021) but provide a novel contribution by highlighting how the media simultaneously legitimize and criticize government policies during the early phase of a new administration. The study concludes that media coverage functions as an ideological arena where government, society, and media interact, emphasizing the need for transparency and broader public participation in education policy formulation. Keywords: Critical Discourse Analysis, Media Ideology, Education Policy, Prabowo–Gibran